2010
DOI: 10.1002/etep.427
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of the magnetic field due to underground power cables using an optimized grid

Abstract: In this paper special attention is given to the mitigation of the magnetic field originated by underground power transmission cables. The mitigation system analyzed is composed by a set of n m conductors, parallel to the power cables, forming a grid. An optimization algorithm was developed in order to obtain the best location to install the grid conductors. In order to reduce the number of the unknowns, the algorithm was developed taking into account the symmetry of the system. Results are presented showing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The technique is based on placing an additional mitigation system (conductive passive shield with an aluminium thickness of 4 mm), close to the source of the protected region [9], [19].…”
Section: Mitigation Of Magnetic Field By Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique is based on placing an additional mitigation system (conductive passive shield with an aluminium thickness of 4 mm), close to the source of the protected region [9], [19].…”
Section: Mitigation Of Magnetic Field By Shieldingmentioning
confidence: 99%
“…Authors in [18], suggested an optimized grid composed of a set of nm conductors, parallel to the power cables, to mitigate the MF originated by UPC. Mitigation of magnetic flux density (MFD) of UPC and its conductor term temperature-based FEM is discussed in reference [19]. MF shielding of UPC by an H-shaped shield is adopted in [20].…”
Section: Introductionmentioning
confidence: 99%
“…A different approach is presented in [57] for an underground power system composed of several parallel subconductors, where a deterministic procedure, based on a geometrical indicator, is employed for identifying the optimal sequence arrangement with the lowest MF emissions, showing an important improvement regarding GA computational time. Alternatively, some studies substitute the use of GA in favor of other techniques, such as Sequential Quadratic Programming (SQP) [58], reducing the number of unknowns by using symmetric layouts for the power cables.…”
Section: Underground Power Linesmentioning
confidence: 99%
“…Different solutions have been analyzed to mitigate the magnetic field, in particular for high voltage transmission underground cables. These solutions, which may be included in the area of electromagnetic compatibility, are frequently classified into two groups: 1) "extrinsic methods" where external apparatuses are used such as shields made of ferromagnetic or conductive materials [3]- [8], including grids of insulated conductors [9] or even other technics like mitigation loops [10]; and (2) "intrinsic methods" where cable parameters themselves are under attention for mitigation purposes, for certain phase arrangements or compacting strategies [11].…”
Section: Introductionmentioning
confidence: 99%